Augmented Reality and Information Marketing: Digital Transformation in Increasing Consumer Experience - Lu'lu Ul Maknunah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Augmented Reality has emerged as a transformative technology in digital marketing, reshaping how consumers interact with brands and product information. This study aims to explore the application of Augmented Reality in digital marketing, its impact on consumer experiences, and the effectiveness of related marketing strategies. Employing a qualitative systematic literature review, the research analyzed seven high-quality studies published between 2020 and 2025, selected through a rigorous process using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. The findings reveal that Augmented Reality enhances consumer experiences through personalized interactions, immersive engagement, and seamless integration of physical and digital platforms, fostering trust and loyalty. However, challenges such as high development costs, limited consumer digital literacy, and privacy concerns hinder widespread adoption. These insights highlight the need for user-friendly platforms and ethical data practices to maximize Augmented Reality’s potential. The study concludes that Augmented Reality significantly enriches digital marketing by offering innovative consumer experiences, but its success depends on overcoming technological and accessibility barriers. Future research should explore longitudinal impacts and applications in non-retail sectors to further advance marketing strategies.